MANAJEMEN DAN ANALISA PERANCANGAN SISTEM INFORMASI WEB MOBILE PADA PEMINJAMAN KENDARAAN OPERASIONAL - Katon Abdul Fatah; Mohamad Jamil (Pusat Riset dan Inovasi Nasional, 2021)
Borrowing operational vehicles is currently still done manually, so employees who want to borrow and use operational vehicles for work purposes still have to come to the facilities and infrastructure section to see the availability of vehicles, then fill out the usage form manually, in addition to making loan reports also still use recording into the book. Based on these conditions, this study aims to design an information system for operational vehicle loans. The stages of system development in making this information system use the Prototyping model method which consists of the planning stage, the analysis stage, the design stage, and the implementation stage. Using the PHP programming language in its manufacture and MySQL Server as the database. The result of the research is a mobile web-based operational car loan information system that helps employees and the infrastructure department in the process of borrowing operational vehicles. This information system can also generate operational vehicle loan reports.